Ontologization of mental representations for management purposes - A. R. Akopyan; A. M. Arakelyan; V. V. Krysov (Вестник университета)
The article considers the problems of ontologization of mental representations of a certain field of activity and the corresponding subject area for the purposes of management automation. For the first time, the authors raise the question about the need to include mental representations of the sphere of activity that the subject area reflects in the ontology of the subject area. Ontologization of mental representations is necessary to identify the participants' understanding of their actions, which will change approaches to management, and for deep training of artificial intelligence in order to transfer part of its management functions to it. On the basis of connectionist approaches to understanding thinking, the paper considers the processes of forming mental representations and changing their attributes. The article gives a new definition and typology of mental representations.